Engineering the Unique 2D Mat of Graphene to Achieve Graphene-TiO2 Nanocomposite for Photocatalytic Selective Transformation: What Advantage does Graphene Have over Its Forebear Carbon Nanotube? - Zhang, Yanhui; Tang, Zi-Rong; Fu, Xianzhi; Xu, Yi-Jun (ACS nano, 2011)
Increasing interest has been devoted to synthesizing graphene (GR)-semiconductor nanocomposites as photocatalysts for potential applications, which is very similar to its forebear carbon nanotube (CNT)-semiconductor photocatalysts. Unfortunately, a thoughtful and inevitable comparison between GR- and CNT-semiconductors as photocatalysts is often neglected in literature. This situation may give incomplete or exaggerated information on the contribution role of GR to enhance the semiconductor photocatalytic activity, as compared to CNT. Thus, our knowledge regarding the specific advantage of GR over CNT on how to design more efficient GR-semiconductor nanocomposites and understanding the origin of their enhanced photocatalytic performance is far from satisfactory. By taking the TiO2 semiconductor as an example, we conceptually demonstrate how to synthesize a more efficient GR-TiO2 nanocomposite as a visible light photocatalyst toward selective oxidation of alcohols under mild conditions. Comparison between GR-TiO2 and CNT-TiO2 discloses the prominent advantage of GR over CNT on both controlling the morphology of GR-TiO2 nanocomposite and enhancing the photocatalytic activity of TiO2. This work clearly highlights the importance and necessity for a comparison investigation between GR- and CNT-semiconductors as photocatalysts, which will promote our in-depth fundamental understanding on the analogy and difference between GR and CNT on controlling the morphology of GR (or CNT)-semiconductor nanocomposites and enhancing the photocatalytic performance. Therefore, we appeal the photocatalysis community to pay attention to this respect rather than separately imposing hype on the miracle of GR in much the same way as its carbon forebears, which could significantly advance our rational fabrication of smart GR-semiconductor nanocomposites for artificial photosynthesis.